Asymmetric vinylogous michael reaction of cyclic enones with silyloxy furans - Jadhav, Amol P.; Rao, V. U. Bhaskara; Singh, Pradeep; Gonnade, Rajesh G.; Singh, Ravi P. (Chemical Communications, 2015)
The asymmetric vinylogous Michael reaction of cyclohexenone/medium and large cyclic enones with 2-silyloxyfuran is still a synthetic challenge. In this report, we have explored 1,4-conjugate addition of an enantioselective chiral, primary diamine catalyzed, 2-silyloxy furan to various cyclic enones and beta-substituted cyclic enones. The reaction provided syn-Michael adducts (cycloalkane connected gamma-butenolide) with good yields, diastereo and enantioselectivities. Furthermore, the synthetic potential of these syn-Michael adducts is demonstrated by 1,4-addition of nucleophiles on the butenolide substructure.